Long-term results of invasive and non-invasive treatment strategies in the elderly patients with acute coronary syndrome - R.R. Komorovsky (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate long-term outcomes of conservative (optimised medical therapy) versus revascularization strategy of elderly patients with acute coronary syndrome in a real world practice. Materials and methods. Prospective analysis of event-free survival of 113 consecutive patients with acute coronary syndrome aged ≥ 70 years. Study end-points: cardiac death, non-fatal myocardial infarction, unstable angina pectoris, re-hospitalisation. Results. Overall, event-free survival (freedom from death, myocardial infarction, unstable angina or re-hospitalisation) was 59 % at 20 (12–25) months follow-up. The incidence of these events was significantly higher (p = 0.03) in patients receiving only medical therapy compared with those who underwent coronary artery bypass grafting surgery and borderline higher (p = 0.08) compared to percutaneous coronary intervention group patients. The event-free survival rates in both invasively treated groups of patients were not different (p = 0.81). The incidence of soft events, including unstable angina pectoris or re-hospitalisation, was significantly lower in the coronary artery bypass grafting group (р = 0.04) as compared with the medical therapy group, while the incidence of hard events (cardiac death and non-fatal myocardial infarction) was similar in all groups. According to Cox proportional hazard analysis, low ejection fraction (< 40 %) and concomitant peripheral arterial disease were found to be independent predictors of hard events. Conclusion. Coronary artery bypass grafting in the elderly (aged ≥ 70 years) patients appears to be superior to conservative strategy in terms of event-free survival.